GRI Index FY09 - World Bank (Washington, DC, 2015)
The response to the GRI Indicators presents a glimpse into the World Banks (also known as the International Bank for Reconstruction and Development or IBRD in the capital market) complex suite of activities. Topics that are of interest to sustainable investment communities, NGOs, and country clients determine materiality for the purposes of this report. Reporting priorities are determined annually based on the corporate priorities of the given year and queries by the SRI community. Stakeholders are also identified with the assistance of relevant departments throughout the Bank. This Review encompasses World Bank operations globally. The World Bank consists of two agencies: IBRD and IDA (International Development Agency). Except for the terms of lending to member countries, the agencies are tightly integrated and work as a single unit. Therefore, staff of the World Bank, are considered ‘IBRD’ staff, even if they work on IDA funded projects or for other donor-funded initiatives, through hundreds of trust funds. Similarly, World Bank manages the buildings that house staff that work on IBRD, IDA, MIGA, and GEF projects. GRI indicators for EN apply primarily to performance of Washington, D.C. facilities (which house 60 percent of World Bank staff) with country office data noted, when relevant.